Three Patients With Lafora Disease: Different Clinical Presentations and a Novel Mutation. (May 2015) - Poyrazoğlu, Hatice Gamze; Karaca, Emin; Per, Hüseyin; Gümüs, Hakan; Onay, Huseyin; Canpolat, Mehmet; Canöz, Özlem; Ozkınay, Ferda; Kumandas, Sefer
Lafora disease is a rare, fatal, autosomal recessive hereditary disease characterized by epilepsy, myoclonus and progressive neurological deterioration. Diagnosis is made by polyglucosan inclusion bodies (Lafora bodies) shown in skin biopsy. Responsible mutations of Lafora disease involves either the EPM2A or NHLRC1 ( EPM2B ) gene. Mutations in the NHLRC1 gene are described as having a more benign clinical course and a later age of death compared with EPM2A mutations. We report 2 genetic mutations and clinical courses of Lafora disease in 3 adolescents with homozygote NHLRC1 mutation and novel homozygous EPM2A mutation.